Branching patterns of the afferent branchial arteries and their phylogenetic significance in rays (Batoidea) - Karla D. A. Soares (Nature Portfolio, 2021)
Abstract Rays of the superorder Batoidea comprise the most diverse group of chondrichthyans in terms of valid species and morphological disparity. Up to the present little agreement is observed in studies based on morphological and molecular data focused on uncovering the interrelationships within Batoidea. Morphology-based phylogenies of batoids have not included characters related to the afferent branchial arteries, and little is known about the variation in this anatomical complex in rays. Herein, representatives of 32 genera from 19 families currently recognized of rays were examined as well as some shark taxa. Seven new characters are proposed and tested in two different analyses, one on their own and in the other they were added to the morphological data matrix of the most recent analysis of interrelationships within Batoidea. The arrangement of afferent branchial arteries differs mainly among orders and families of batoids. The absence of a common trunk from which the three posteriormost afferent arteries branch is interpreted as a synapomorphy for Myliobatiformes and the presence of a coronary cranial artery as an autapomorphy for Mobula hypostoma. A close spatial relationship between the second and third afferent arteries within the common branch from the ventral aorta is proposed as a synapomorphy for Rajiformes with a secondary modification in Sympterygia. Data about patterns in afferent branchial arteries in additional taxa such as Squaliformes and Chimaeriformes are needed to better understand the evolution of this character complex among chondrichthyans.